Memberdayakan ELSA SPEAK: Pendekatan Modern untuk Menguasai Berbicara dan Pelafalan Bahasa Inggris dengan Teknologi AI untuk Siswa Bahasa Inggris sebagai Bahasa Asing - Naura Ariesta; Shifa Mantika Nur Aulia; Yulian Purnama (Tarling : Journal of Language Education, 2025)
This study critically analyses the ELSA Speak application and its multifaceted impacts on the development of speaking and pronunciation skills among English as a Foreign Language (EFL) learners. EFL students often encounter persistent challenges such as limited exposure to authentic native-speaking environments, anxiety related to fear of negative evaluation, and predominantly passive learning processes that hinder oral proficiency. The ELSA Speak app effectively addresses these barriers by providing immediate, personalized, and detailed feedback on various critical components of spoken English, including pronunciation accuracy, intonation patterns, speech rhythm, word stress, grammatical correctness, lexical choice, and overall fluency. Employing a comprehensive literature review methodology, this study synthesizes findings from 14 peer-reviewed academic articles published between 2019 and 2024, which investigate the app’s speaking modules designed to simulate real-life communicative contexts and its autonomous learning features enhanced by gamified progress tracking systems. The evidence indicates that ELSA Speak significantly enhances learners’ pronunciation precision and oral fluency, while concurrently boosting their self-confidence and intrinsic motivation to engage in language practice. Furthermore, the application mitigates chronic speaking difficulties commonly faced by EFL learners and facilitates improved performance in authentic communicative interactions. By integrating well-established pedagogical frameworks with cutting-edge artificial intelligence technology, ELSA Speak offers an innovative, efficient, and scalable solution to address existing gaps in EFL instruction. This study contributes valuable insights into the potential of AI-driven language learning tools to transform traditional language pedagogy and foster more effective, learner-centered approaches in the digital age.